Relative Efficiency of Education, Health, and Infrastructure Spending in Southeast Sulawesi (2018–2022): A Data Envelopment Analysis Approach - Siti Hajarana; Muhammad Tojibussabirin; Yeney Widya Prihatiningtias (Al-Qalam Institute, 2025)
This study aims to analyze the relative efficiency of education, health, and infrastructure spending in Southeast Sulawesi Province. During the 2018–2022 period, the province experienced relatively strong economic growth along with increased public spending, but gaps in outcomes and sectoral performance between districts remained evident. This study employed a quantitative approach using Data Envelopment Analysis (DEA) with an input-output orientation. A balanced panel dataset of 17 districts/cities observed over five years (85 Decision-Making Units) was analyzed to measure the relative efficiency of education, health, and infrastructure spending. The results indicate that the average efficiency of education (0.97) and health (0.98) spending is higher than that of infrastructure (0.79). Urban areas and optimally planned areas exhibit full efficiency (score 1.00), while remote areas experience relatively suboptimal efficiency levels. Some districts consistently achieve full efficiency, indicating effective resource allocation and service delivery. Conversely, geographically remote areas exhibit inefficiencies due to the uneven distribution of teachers, health workers, and infrastructure quality. These findings suggest that high levels of spending do not automatically guarantee optimal welfare outcomes. This study contributes by providing a subnational efficiency assessment using DEA and offering policy recommendations focused on targeted allocation, cross-sector integration, and performance-based budgeting.